Intermediating R&D and Marketing Value Creation by Open Innovation - Wang, Shu; Chen, Jin; Xie, Fang (Proceedings of IEEE International Conference on Industrial Engineering and Engineering Management, 2011)
Based on the open innovation theory the paper explores several notable enterprises' behavior from high-tech products to service providers, and by comparing and contrasting the use of the service-based organizations and external R&D-related activities in companies at home and abroad, it pointed out how an eco-community or commercial system can make it possible for the firms looking for service and business to accomplish the external R&D-related activities and marketing objectives. And by discussing the panel data of R&D expenditure of companies in China, the paper analyses what kind of strategy and effort should be taken for attract the complement resources from OI eco-community, especially by the firms' appetite survey for OI process, it can be seen that inexorable R&D and marketing service make social technology more important over time in some developing economies which make the subject area of service and relationships a particularly important one for marketing value creation.<br
Keywords: open innovation; R&D; neo-schumpeterian